Icbf closer to the citizen (2017)
This paper presents the importance of the relationship with the external client from the point of view of a state entity such as the Colombian Institute of Family Welfare - ICBF, showing the structural change in the entity and the social responsibility into the organization. In the same way, initiatives are presented to improve interest and provision of service with a timely attention and vision to be a model Institution in the provision of its services and thus to improve quality of life of Colombian children and the family, to be recognized nationally and internationally for its excellent levels of effectiveness and quality team that provides the service with warmth, affection and transparency.